ANALYSIS OF THE OUTCOMES FOR THE TREATMENT OF POST-TRAUMATIC STRESS DISORDER AMONG CHILDREN AND ADOLESCENTS: SYSTEMATIC REVIEW - Shubina, Ivanna (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: Emerging evidence in the treatment of post-traumatic stress disorder (PTSD) points to a significant role of exposure therapy and cognitive-behavioral approaches, yet current theoretical and empirical background remains relatively disparate. The current systematic review aimed to synthesize, describe, and critique evidence demonstrating the outcomes for the treatment of PTSD in adolescent and child populations. Method: Systematic searches of computerized databases, top-ranked journals, searches of reference lists were conducted to identify randomized controlled trials of treatment of PTSD among children and adolescents.  Results: Twenty-one papers were identified. The criteria for article selection, strategy and process of inclusion studies into a systematic review, as well as the main characteristics of studies on the effectiveness of psychological treatments for PTSD discussed. Conclusions. Although findings were mixed, this review suggests that psychological treatments can reduce symptoms of PTSD. It supports the current emerging tendency stating the importance of the development of a unified framework PTSD for treatment in the chosen age group.